PENGARUH VARIASI KONSENTRASI MEDIA PENDINGIN (QUENCHANT) PADA PROSES QUENCH TERHADAP KEKERASAN, STRUKTUR MIKRO DAN RETAK AKIBAT QUENCH (QUENCH CRACK) DARI BAJA AISI 1040 - Dharma Surya; Sitompul D Edmond (ROTOR, 2018)
Cracks during the quench process are a common problem. There are several observational parameters in the heat treatment process to succeed, namely the chemical composition of steel and its hardness, the geometry of the components, mechanical handling, the type of cooling fluid, the temperature of the cooling fluid, the conditions of the coolant, the circulation of the cooling media. In mass production, for example, bolt production in the quench process is more dominant in smaller diameters than As Bar compared to larger diameters. In this study, mechanical properties such as hardness, physical properties such as microstructure and cracking were considered as a function of the quenching conditions of AISI 1040 steel with a diameter of 25mm after hardening process at 850oC with the influence of quenchant concentration variations investigated. The microstructure of as-quench martensite and its development during the Hardening process is observed. The results showed changes in hardness and microstructure as well as cracks that occurred from specimens due to the hardening process on Quenchant Variation Key Words: Hardness, Heat Treatment, Quench, Quench Crack, Quenchant